Alternative Politics and Gramsci’s Hegemonic Theory: A Study in the Context of Nepal - Magar, Rudra Bahadur Pulami (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
The Manuscript explores the rise of alternative politics in Nepal through the lens of Antonio Gramsci’s hegemony. It examines how new political movements, particularly the Gen Z Movement of 2025, challenge the dominance of traditional parties drawing from Gramsci’s ideas of hegemony and counter-hegemony, the study argues that alternative politics in Nepal represents a cultural and ideological struggle against entrenched political power rather than a mere quest for leadership change. Using a qualitative and analytical approach based on secondary sources, the research employs thematic content analysis to study political discourse, youth activism, digital movements, and civil society engagement. It investigates how Gen Z’s digital activism and social media campaigns have created a new counter-hegemonic space, reshaping Nepal’s political consciousness. The literature review situates this movement within global and Nepali contexts, emphasizing gaps in existing studies that overlook the connection between Gramsci’s theory and Nepal’s political transformations. Through qualitative analysis, it explores Gen Z’s role in building counter-hegemonic structures that emphasize accountability and participatory democracy. The study concludes that alternative politics, if institutionalized, could reshape Nepal’s democratic culture and governance.